Distortions and the size distribution of plants: Evidence from cross-country data - Manuel García-Santana; Roberto Ramos (SERIEs - Journal of the Spanish Economic Association, 2015)
We study the relationship between economic distortions and the size distribution of plants using comparable plant-level data across 104 developing countries. Our main result is to show that, other things equal, countries with larger economic distortions allocate more labor to small unproductive units. By decomposing the business environment into different type of distortions, we find that poor access to financial credit is the one driving our results.We also show that there exists a significant crosscountry relationship between the size distribution and aggregate productivity. These results are consistent with a large recent literature on misallocation of resources across firms.
Keywords: L11; L53; O47; 330; TFP; Plant size distribution; Economic distortions